[18F]FDG-PET scan in patients with fasting hyperglycemia - Belohlavek, Otakar; Jaruskova, Monika (The Quarterly journal of nuclear medicine and molecular imaging, 2016)
BACKGROUND: It is generally accepted that a non-fasting state reduces [18F]FDG-PET quality, but the significance of higher levels of fasting blood glucose has aroused some doubts over time. The aim of this work was to provide further evidence to clarify this issue and its impact on the handling of hyperglycemic patients in daily routine. METHODS: Muscle and liver standardized uptake values (SUV) and their ratio, tumor SUV and the frequency of positive PET findings were retrospectively analyzed in 116 hyperglycemic (HG) patients (>11 mmol/L), in 116 patients with slightly elevated glycemia (SEG) (5.6-7.0 mmol/L) and in 116 normoglycemic (NG) patients (4.7 mmol/L). RESULTS: No significant difference was found in the muscle to liver ratio, in muscle SUV and in the frequency of positive PET findings among HG, SEG and NG patients. HG patients exhibited ~10% higher liver SUV in comparison to SEG and NG patients; a positive correlation (r=0.2849) was found between liver SUV and blood glucose levels. Significantly higher tumor SUV was present in SEG patients. CONCLUSIONS: We did not confirm that hyperglycemia in a fasting state negatively influences the diagnostic quality of [18F]FDG-PET. The positive correlation between liver SUV and blood glucose levels is clinically negligible and might be explained by increased fasting hepatic gluconeogenesis in diabetics. Our data encourage the performance of [18F]FDG-PET investigations under fasting conditions, regardless of the mild to medium elevation of fasting blood glucose level.
Keywords: Muscles; hyperglykemie; Male; retrospektivní studie; Positron-Emission Tomography; pozitronová emisní tomografie; mužské pohlaví; Hyperglycemia; fluorodeoxyglukosa F18; lidé; omezení příjmu potravy; svaly; ženské pohlaví; játra; Fluorodeoxyglucose F18; Humans; Fasting; Retrospective Studies; Liver; Female; lidé středního věku; Middle Aged